2007
DOI: 10.2175/106143006x111862
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Time for Pathogen Inactivation in Alkaline Disinfection Systems Using Pressure

Abstract: From field studies conducted by Tulane University (New Orleans, Louisiana), efficiency of advanced alkaline disinfection in closed systems was found to depend on ammonia concentration, pH, exposure time, temperature, total solids content, pretreatment storage time, and mixing effectiveness. In this study of a closed alkaline system, an additional pathogen stressor pressure was tested. The effect of the alkaline dosing has been assessed for dewatered raw and aerobically and anaerobically digested municipal slud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Generally, addition of lime to faecal sludge releases ammonia which assists in the destruction of pathogens specifically coliforms [10,11] as cited by Spit et al [12]. The containment of ammonia in the reactor acts as a biocide that further kills pathogens [13]. Pathogen reduction for lime treatment is achieved by the high pH levels and the ammonia concentration induced through the addition of lime [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, addition of lime to faecal sludge releases ammonia which assists in the destruction of pathogens specifically coliforms [10,11] as cited by Spit et al [12]. The containment of ammonia in the reactor acts as a biocide that further kills pathogens [13]. Pathogen reduction for lime treatment is achieved by the high pH levels and the ammonia concentration induced through the addition of lime [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…At pH levels greater than 12, the cell membranes of harmful pathogens are destroyed [ 18 ]. The high pH also leads to high fractions of non-ionised ammonium which, as detailed in the previous urea treatment section, will act as a biocide and contribute to pathogen removal if contained within the reactor [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pilot testing was conducted at Tulane University in 2004 and indicated that the Bioset process met the criteria for a PEC process to disinfect to Class A (Fitzmorris et al 2007). This data is capsulated in Table 1.…”
Section: Resultsmentioning
confidence: 99%